Investigation of Health Promotion Behaviors among the Elderly - Sakineh Gerayllo; Mohammad taghi Badeleh; Somayeh Ghorbani; Alireza Arab (Journal of Social Behavior and Community Health, 2025)
Background: Performing health-promoting behaviors is the most important and effective factor in maintaining the health of the elderly. Therefore, this study investigated health promotion behaviors and their related factors among the elderly population in Gorgan city. Methods: This cross-sectional descriptive-analytical study was conducted in 2023. Using a multistage sampling method, four comprehensive health centers in Gorgan city, Iran, were randomly selected, and a total of 170 elderly individuals aged over 60 years were conveniently recruited into the study. Data were collected using the standardized Health-Promoting Lifestyle Profile II (HPLP–II) questionnaire. After data collection, the data were analyzed and reported using SPSS version 26 software and parametric statistical tests, including t-test, ANOVA, and Pearson correlation coefficient, at a significance level of less than 0.05. Results: In this study, 44.1% of the elderly were male and 55.9% were female. The mean age of the participants was reported as 66.70 ± 7.23 years. A statistically significant difference was observed between the mean score of health promotion behaviors and demographic variables, including education level, economic status, and presence of underlying diseases (p < 0.05). Pearson correlation results indicated a positive correlation between health promotion behaviors and their subdomains (p < 0.05). The highest mean score was related to the interpersonal relations domain (32.28), while the lowest score belonged to the physical activity domain (13.52). Conclusion: Considering the results and the importance of health-promoting behaviors, particularly the low average scores in physical activity and stress management, it is necessary to emphasize these areas. Implementing continuous education programs based on elderly surveys, alongside strategic planning to encourage their active participation in health-related matters, can enhance health promotion among the elderly population.